Association between personal exposure to ambient metals and respiratory disease in Italian adolescents: a cross-sectional study. Issue 1 (December 2016) - Rosa, Maria; Benedetti, Chiara; Peli, Marco; Donna, Filippo; Nazzaro, Marco; Fedrighi, Chiara; Zoni, Silvia; Marcon, Alessandro; Zimmerman, Neil; Wright, Rosalind; Lucchini, Roberto
Abstract Background Release of ambient metals during ferroalloy production may be an important source of environmental exposure for nearby communities and exposure to these metals has been linked to adverse respiratory outcomes. We sought to characterize the association between personal air levels of metals and respiratory health in Italian adolescents living in communities with historic and current ferroalloy activity. Methods As part of a study in the industrial province of Brescia, Italy, 410 adolescents aged 11–14 years were recruited. Participants were enrolled from three different communities with varying manganese (Mn) levels: Bagnolo Mella which has current ferroalloy activity, Valcamonica, which has historic ferroalloy activity and Garda Lake which has no history of ferroalloy activity. Particulate matter <10 μm in diameter (PM10 ) was collected for 24 h in filters using personal sampling. Mn, nickel (Ni), zinc (Zn), chromium (Cr) and iron (Fe) were measured in filters using x-ray fluorescence. Data on respiratory health was collected through questionnaire. Data for 280 adolescents were analyzed using a modified Poisson regression, and risk ratios were calculated for an interquartile (IQR) range increase in each pollutant. Results In adjusted models including PM10 as a co-pollutant, we found significant associations between concentrations of Mn (RR: 1.09, 95 % CI [1.00, 1.18] per 42 ng/m3 increase), Ni (RR: 1.11, 95 % CI [1.03, 1.21] per 4 ng/m3 increase) and Cr (RR: 1.08, 95 % CI [1.06, 1.11] per 9 ng/m3 increase) and parental report of asthma. We also found significant associations between increased Mn and Ni and increased risk of asthma medication use in the past 12 months (RR: 1.13, 95 % CI [1.04, 1.29] and (RR: 1.13, 95 % CI [1.01, 1.27] respectively). Conclusions Our findings suggest that exposure to ambient Mn, Ni and Cr may be associated with adverse respiratory outcomes.